Pengaruh Brand Image dan Kualitas Layanan Terhadap Keputusan Pembelian pada Supermarket Matahari Praya - Assa’ady, M. Chothibul Umam; Talidobel, Susilo; Wardi, Putri Amalia (Varied Knowledge Journal, 2024)
This study aims to investigate the influence of brand and service quality on consumer purchasing decisions. This study was conducted at Matahari supermarket in Praya City by collecting data from a number of respondents who are active consumers. This research uses a quantitative approach by distributing questionnaires to 112 respondents. Data collection was conducted through a survey method using a Likert scale to measure consumer perceptions related to brand, service quality and purchasing decisions. Data analysis techniques The research data was tested by SmartPLS 0.3 analysis testing with the auter model analysis test, inner model and hypothesis testing. The results of this study indicate the X1->Y1 hypothesis that the T Statistic value is 0.550 and the P Values value is 0.580, which means it is rejected, brand image has no effect on purchasing decisions and the X2->Y1 hypothesis that the T Statistic value is 9.919 and the P Values value is 0.000, which means it is accepted, service quality affects purchasing decisions. This research provides understanding in increasing our knowledge of how customer purchasing decisions can be influenced by brand image and service quality. The conclusion of this research is that to influence customer purchasing decisions, businesses must build their brand image and improve the quality of the services they offer.